GOOD GOVERNANCE FOR ZAKAH, INFAQ, AND SADAQAH (ZIS) COLLECTION WITHIN LOCAL COMMUNITIES:A CASE STUDY IN GORONTALO REGENCY - Ladiku, Hamdan; Zaman, Akhmad Roja Badrus (Al-Qalam, 2024)
This study endeavors to present a comprehensive overview of how the implementation of Good Governance impacts the collection of zakat, infaq, and alms for local communities. Qualitative descriptive research methodology was employed, drawing insights from various regulatory frameworks and empirical evidence. The findings reveal several key points: Firstly, the presence of accommodating regulations serves as a legal framework for local institutions, coupled with tangible financial incentives that motivate effective collection of ZIS (zakat, infaq, sadaqah). Secondly, the upsurge in zakat, infaq, and alms collection is not solely reliant on spiritual enlightenment but is significantly influenced by regulatory frameworks that stimulate the optimization of local institutions. Lastly, to ensure the efficacy of the collection process, the government undertakes collaborative evaluations involving stakeholders such as the Indonesian Ulema Council (MUI), academicians, Mahad Jamiah, and the Zakat Empowerment Team. These findings underscore the importance of formulating progressive policies geared towards enhancing the collection of zakat, infaq, and alms, providing valuable insights for policymakers